2005
DOI: 10.1074/jbc.m408851200
|View full text |Cite
|
Sign up to set email alerts
|

Cross-interactions of Two p38 Mitogen-activated Protein (MAP) Kinase Inhibitors and Two Cholecystokinin (CCK) Receptor Antagonists with the CCK1 Receptor and P38 MAP Kinase

Abstract: Although SB202190 and SB203580 are described as specific p38 MAP kinase inhibitors, several reports have indicated that other enzymes are also sensitive to SB203580. Using a pharmacological approach, we report for the first time that compounds SB202190 and SB203580 were able to directly and selectively interact with a G-protein-coupled receptor, namely the cholecystokinin receptor subtype CCK1, but not with the CCK2 receptor. We demonstrated that these compounds were non-competitive antagonists of the CCK1 rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…Analyses of kinase inhibitor selectivity often focus on selectivity versus other protein kinases (32) and methods are available to test this (3). Our findings and others (6,7) show that additional, non-ATP-dependent proteins may also mediate off-target effects of kinase inhibitors.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Analyses of kinase inhibitor selectivity often focus on selectivity versus other protein kinases (32) and methods are available to test this (3). Our findings and others (6,7) show that additional, non-ATP-dependent proteins may also mediate off-target effects of kinase inhibitors.…”
Section: Discussionmentioning
confidence: 86%
“…Studies of inhibitor specificity typically examine cross-reactivity against other protein kinases (3) or low-potency effects against target panels involved in liabilities (4). However, recent publications illustrate that kinase inhibitors are also capable of potent interactions that affect the function of additional protein classes (5)(6)(7)(8). For example, an inhibitory activity of imatinib and nilotinib on the oxidoreductase enzyme Nqo2 has been shown; this activity is not shared with dasatinib (5, 7), a third kinase inhibitor approved in chronic myelogenous leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using pancreatic fragments stimulated by the CCK analog, cerulein, have shown that pro-inflammatory mediator production increased in parallel with activation of p38 and that these changes were attenuated by chemical inhibitors of p38 (22). However, chemical inhibitors of p38 MAP kinase may lack specificity as suggested by recent reports that they also inhibit the CCK-A cell surface receptor (23). Therefore, utilizing genetic manipulation via over expression of an adenoviral vector expressing DN p38 is a superior method of modulating p38 MAP kinase with respect to the non-specificity of chemical inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Because SB202190 affects both Akt and p38͞MAPK phosphorylation, the complete reduction in TSP-1 induced by ATP could be a result of the combinatorial effect of blocking both Akt and p38͞MAPK signaling. We have considered the possibility that MAPK pathway inhibitors may affect functions of P2Y receptors such as receptor activation or G protein coupling because it has been reported that SB202190 can directly interact with the G protein-coupled receptor subtype CCK1, although not with the CCK2 subtype (45). However, the other kinase inhibitors we have used, U0126, wortmannin, and SP600125, are structurally unrelated to SB202190.…”
Section: Discussionmentioning
confidence: 99%